STRUKTUR KOMUNITAS HUTAN MANGROVE STRATA POHON (TREE) DAN TIANG (POLE) DI DESA TELUK PAMBANG KABUPATEN BENGKALIS SEBAGAI RANCANGAN HANDOUT PADA MATERI EKOSISTEM KELAS X SMA - Suria Mutaqin; Yuslim Fauziah; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Research has been conducted to determine the composition and structure of tree and pole strata vegetation in the mangrove forest of Teluk Pambang Village, Bengkalis Regency in March-November 2018. The research used a survey method and Belt Transec along 100 m with an observation plot measuring 20 x 20 m for tree strata and 10 x 10 m for pole strata. The parameters in this study are the composition of type, density, frequency, dominance, important value, and diversity index. The result of research showed that there were 15 species of mangrove forests in Teluk Pambang Village, namely Xylocarpus granatum, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, Bruguiera cylindrica, Bruguiera gymnorrhiza, Bruguiera sexangula, Bruguiera parviflora, Ceriops tagal, Ceriops decandra, Lumnitzera littorea , Sonneratia alba, Sonneratia caseolaris, Avicennia alba, and Scyphypora hydrophyllacea. The important value index of influential tree strata are Xylocarpus granatum (St.I), Bruguiera cylindrica (St.II and III), Rhizophora apiculata (St. IV) and Sonneratia alba (St.V). In the pole strata of the influential species, Bruguiera cylindrica (St.I, II and III), Rhizophora apiculata (St. IV) and Avicennia alba (St.V). Diversity index of mangrove tree strata and pole vegetation in the mangrove forest area of Bengkalis Regency, which ranged from 0.64 to 1.98 for tree strata and 1.01-2.13 for pole strata. The results of the study can be used as a handout on the concept of the ecosystem.Keyword : Composition Of Type, Vegetation Structure, Handout